Modified positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611145291.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明提供了一种改性正极材料及其制备方法和应用,以解决现有正极材料表面存在大量残锂导致容量衰减快,循环性能和倍率性能不佳的问题
1.本发明提供的改性正极材料的制备方法,首先将正极材料前驱体与锂源混合进行预煅烧,得到表面富含残锂的锂化正极材料;然后将锰源与锂化正极材料在分散剂的存在下进行混合,使锰源均匀、紧密地共形吸附在锂化正极材料颗粒的表面;接着进一步煅烧,在高温的驱动下,表面的Mn4+向颗粒表层晶格内部进行热扩散迁移,激活拓扑锂化机制,使预煅烧阶段自身产生的有害游离残锂进入晶格中进行原位晶格重构,成功将原本有害的残锂转化为了高活性的Li2NiO2富锂超结构包覆层和/或Li2MnO3包覆层,使制得的改性正极材料具有较高的首次充放电比容量和首次库伦效率,同时改善循环稳定性和高倍率下的放电比容量。并且,本发明全过程无需水洗,省去了传统水洗后的废水处理流程,工艺简单,绿色环保,成本低廉,极具工业化大规模生产前景。
Smart Images

Figure CN122916232A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery materials technology, specifically to a modified cathode material, its preparation method, and its application. Background Technology
[0002] To meet the demand for ultra-high energy density power batteries in humanoid robots, low-altitude aircraft, and electric vehicles, ultra-high nickel layered oxides (such as LiNi) with a nickel content greater than 90% are required. 0.9 Co 0.1 O2) has become the mainstream development direction. However, in the high-temperature synthesis process, in order to suppress Ni 2+ / Li + To achieve cation mixing and compensate for the high-temperature volatilization of lithium, it is usually necessary to add an excess of lithium source (such as LiOH). During cooling or air exposure, this excess lithium source will spontaneously react with H2O and CO2 in the air, forming a large amount of free residual lithium impurities (mainly LiOH and Li2CO3) on the particle surface.
[0003] However, during battery cycling, residual lithium not only hinders the rapid transport of lithium ions, but also reacts with the electrolyte to release a large amount of CO2 gas, causing battery swelling and the generation of HF, which exacerbates the dissolution of transition metals and the destruction of oxygen lattice, resulting in rapid capacity decay and significantly poor cycle performance and rate performance.
[0004] Therefore, there is an urgent need for a modified cathode material that can effectively mitigate the impact of residual lithium and synergistically improve cycle performance and rate performance. Summary of the Invention
[0005] This invention provides a modified cathode material, its preparation method, and its application, to solve the problem that existing cathode materials have a large amount of residual lithium on their surface, leading to rapid capacity decay and poor cycle performance and rate performance.
[0006] In a first aspect, the present invention provides a method for preparing a modified cathode material, comprising the following steps: Step S1: Mix the cathode material precursor and the lithium source in the first stage, and pre-calcine to obtain the lithium-ion cathode material; Step S2: The lithium-ion cathode material, manganese source and dispersant are mixed for the second time and dried to obtain the intermediate product; Step S3: Calcine the intermediate product to obtain the modified cathode material.
[0007] In one optional embodiment, the molar ratio of total metal elements in the cathode material precursor to manganese elements in the manganese source is 1:0.02-0.05, preferably 1:0.03-0.05.
[0008] In one optional embodiment, the chemical formula of the cathode material precursor is Ni. x Co 1-x (OH)2, where 0.9≤x≤0.94.
[0009] In one optional embodiment, the molar ratio of total metal elements in the cathode material precursor to lithium elements in the lithium source is 1:1.05-1.08, preferably 1:1.06.
[0010] In one alternative embodiment, the lithium source comprises lithium hydroxide monohydrate and / or lithium carbonate.
[0011] In one optional embodiment, the mass ratio of the cathode material precursor to the dispersant is 1:1-1.5.
[0012] In one optional embodiment, the manganese source includes at least one of manganese dioxide, manganese hydroxide, and manganese hydroxyoxide.
[0013] In one alternative embodiment, the dispersant includes at least one of ethanol, ethylene glycol, and polyvinyl alcohol.
[0014] In one alternative embodiment, the first mixing speed is 1000-1500 rpm and the time is 20-30 min.
[0015] In one alternative embodiment, the pre-calcination operation includes heating from room temperature to 300-400°C at a heating rate of 1-3°C / min under an oxygen atmosphere, and holding at that temperature for 4-8 hours.
[0016] In one alternative embodiment, the second mixing speed is 250-350 rpm, and the time is 4-8 h.
[0017] In one optional embodiment, the drying temperature is 100-120°C and the time is 2-4 hours.
[0018] In one optional embodiment, the calcination operation is carried out in an oxygen atmosphere, heating from room temperature to 500-600°C at a heating rate of 1-3°C / min, holding at that temperature for 4-8 hours, and then continuing to heat to 700-800°C at a heating rate of 1-3°C / min, holding at that temperature for 12-18 hours.
[0019] Secondly, the present invention provides a modified cathode material prepared by the above-mentioned method for preparing modified cathode materials.
[0020] In one optional embodiment, the modified cathode material includes a cathode material matrix and a coating layer covering the surface of the cathode material matrix; the coating layer includes Li2NiO2 and / or Li2MnO3.
[0021] Thirdly, the present invention provides a positive electrode sheet, comprising: Positive current collector, and A positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the modified positive electrode material prepared by the above preparation method or the above modified positive electrode material.
[0022] Fourthly, the present invention provides a secondary battery comprising the aforementioned positive electrode sheet.
[0023] Fifthly, the present invention provides an electrical device comprising the aforementioned secondary battery.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The method for preparing modified cathode material provided by the present invention firstly involves mixing a cathode material precursor with a lithium source and pre-calcining to obtain a lithium-ionized cathode material with a surface rich in residual lithium; then, a manganese source is mixed with the lithium-ionized cathode material in the presence of a dispersant, so that the manganese source is uniformly and tightly conformally adsorbed on the surface of the lithium-ionized cathode material particles; subsequently, further calcination is performed, and under high temperature, the Mn on the surface... 4+ Thermal diffusion migration into the particle surface lattice activates the topological lithiation mechanism, allowing harmful free residual lithium generated during the pre-calcination stage to enter the lattice for in-situ lattice reconstruction. This successfully transforms the originally harmful residual lithium into a highly active Li2NiO2 lithium-rich superstructure coating layer and / or Li2MnO3 coating layer. This results in a modified cathode material with higher initial charge-discharge specific capacity and initial coulombic efficiency, while also improving cycle stability and discharge specific capacity at high rates. Furthermore, this invention eliminates the need for water washing throughout the entire process, avoiding the wastewater treatment process required by traditional water washing. The process is simple, environmentally friendly, and low-cost, making it highly promising for large-scale industrial production.
[0025] 2. The method for preparing the modified cathode material provided by this invention, when the molar ratio of manganese element in the manganese source to the total metal elements in the cathode material precursor is 1:0.03-0.05, a Li2MnO3 coating layer will be generated in situ on the outermost layer of the cathode material. Because Li2MnO3 has extremely strong Mn-O bonds, it can effectively block high-valence Ni... 4+ By suppressing the side reactions with the electrolyte and inhibiting intergranular cracking under high-voltage charge and discharge, the modified cathode material can be made to have better cycle performance and rate performance. Attached Figure Description
[0026] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0027] Figure 1 This is a high-magnification scanning electron microscope image of the modified cathode material prepared in Example 1 of the present invention; Figure 2 This is a high-resolution transmission electron microscope image of the modified cathode material prepared in Example 1 of the present invention; Figure 3 This is a high-magnification scanning electron microscope image of the modified cathode material prepared in Example 2 of the present invention; Figure 4 This is a high-resolution transmission electron microscope image of the modified cathode material prepared in Example 2 of the present invention; Figure 5 This is a high-magnification scanning electron microscope image of the modified cathode material prepared in Comparative Example 1 of this invention. Detailed Implementation
[0028] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.
[0029] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0030] Example 1 This embodiment provides a method for preparing a modified cathode material, including the following steps: (1) Ni 0.9 Co 0.1 (OH)2 cathode material precursor and LiOH•H2O were uniformly mixed at 1500 rpm for 30 min at a molar ratio of 1:1.06. Then the mixture was placed in a tube furnace and heated from room temperature to 350℃ at a heating rate of 2℃ / min under a pure oxygen atmosphere. The mixture was then pre-calcined at a constant temperature for 6 h to obtain the lithium-ion cathode material. (2) After the above-mentioned lithium-ion cathode material is naturally cooled, high-purity manganese dioxide powder (purity of 99.9%) is added according to the molar ratio of total metal elements in the cathode material precursor to manganese elements in manganese dioxide of 1:0.02; then anhydrous ethanol of the same mass as the cathode material precursor is injected as a dispersant, the mixture is loaded into an agate ball mill jar, and wet ball milled at 300 rpm for 6 hours on a ball mill to ensure that MnO2 achieves micro-uniform and tight adsorption and coating on the surface of the lithium-ion cathode material particles. After drying at 110°C for 3 hours, an intermediate product is obtained. (3) The intermediate product is transferred into an oxygen atmosphere furnace for further calcination to achieve solid-state lattice reconstruction. The calcination procedure is as follows: first, heat from room temperature to 550°C at a heating rate of 2°C / min and hold for 6 hours; then continue heating to 750°C at a heating rate of 2°C / min and sinter at high temperature for 16 hours. After cooling, the modified cathode material is obtained, denoted as NC@2Mn.
[0031] Depend on Figure 1 and Figure 2 It can be seen that the modified cathode material prepared in this embodiment has a micro-uniform and dense adsorption coating layer on its surface, according to Figure 2 The lattice fringes data clearly show a novel and highly ordered lattice fringes in the surface region (Surface Region Ⅰ) of NC@2Mn particles, with an interplanar spacing of 0.257 nm. This interplanar spacing perfectly corresponds to the (002)p crystal plane of the Li2NiO2-type lithium-rich superstructure with the P-3m1 space group, proving that an active Li2NiO2 coating layer was generated in situ on the subsurface of the particles.
[0032] Example 2 This embodiment provides a method for preparing a modified cathode material, which is basically the same as that in Example 1, except that the amount of manganese dioxide added is different. In this embodiment, high-purity manganese dioxide powder is added according to the molar ratio of total metal elements in the cathode material precursor to manganese elements in manganese dioxide of 1:0.03. The final modified cathode material is denoted as NC@3Mn.
[0033] Depend on Figure 3 and Figure 4 As can be seen, the modified cathode material prepared in this embodiment exhibits a double coating layer on its surface. The first coating layer near the core includes a Li2NiO2 superstructure, and a second coating layer including Li2MnO3 is coated outside the first coating layer. According to Figure 2The lattice fringes data of the second coating layer (i.e. the thin coating layer marked by the green dashed line) of the NC@3Mn cathode material showed a clear physical shell with an interplanar spacing of 0.212 nm. This interplanar spacing perfectly matches the (040)c crystal plane of monoclinic Li2MnO3 with the C2 / m space group, providing the most intuitive and conclusive evidence of the phase structure.
[0034] Example 3 This embodiment provides a method for preparing a modified cathode material, which is basically the same as that in Example 1, except that the amount of manganese dioxide added is different. In this embodiment, high-purity manganese dioxide powder is added according to the molar ratio of total metal elements in the cathode material precursor to manganese elements in manganese dioxide of 1:0.04.
[0035] Example 4 This embodiment provides a method for preparing a modified cathode material, including the following steps: (1) Ni 0.9 Co 0.1 (OH)2 cathode material precursor and LiOH•H2O were uniformly mixed at 1000 rpm for 20 min at a molar ratio of 1:1.05. Then the mixture was placed in a tube furnace and heated from room temperature to 300℃ at a heating rate of 1℃ / min under a pure oxygen atmosphere. The mixture was then pre-calcined at a constant temperature for 8 h to carry out preliminary lithiation and obtain the lithiated cathode material. (2) After the above-mentioned lithium-ion cathode material is naturally cooled, high-purity manganese dioxide powder (purity of 99.9%) is added according to the molar ratio of total metal elements in the cathode material precursor to manganese elements in manganese dioxide of 1:0.05; then anhydrous ethanol is injected as a dispersant, wherein the mass of anhydrous ethanol is 1.25 times the mass of the cathode material precursor. The mixture is loaded into an agate ball mill jar and wet-milled at 350 rpm for 4 hours on a ball mill to ensure that MnO2 achieves micro-uniform and tight adsorption and coating on the surface of the lithium-ion cathode material particles. After drying at 100℃ for 4 hours, an intermediate product is obtained. (3) The intermediate product is transferred into an oxygen atmosphere furnace for further calcination to achieve solid-state lattice reconstruction. The calcination procedure is as follows: first, heat from room temperature to 600℃ at a heating rate of 3℃ / min and hold for 4h; then continue heating to 800℃ at a heating rate of 3℃ / min and sinter at high temperature for 12h. After cooling, the modified cathode material is obtained.
[0036] Example 5 This embodiment provides a method for preparing a modified cathode material, including the following steps: (1) Ni 0.9 Co 0.1(OH)2 cathode material precursor and LiOH•H2O were uniformly mixed at 1300 rpm for 25 min at a molar ratio of 1:1.08. Then the mixture was placed in a tube furnace and heated from room temperature to 400℃ at a heating rate of 3℃ / min under a pure oxygen atmosphere. The mixture was then pre-calcined at a constant temperature for 4 h to carry out preliminary lithiation and obtain the lithiated cathode material. (2) After the lithium-ion cathode material is naturally cooled, high-purity manganese dioxide powder (purity of 99.9%) is added according to the molar ratio of total metal elements in the cathode material precursor to manganese elements in manganese dioxide of 1:0.03; then anhydrous ethanol is injected as a dispersant, wherein the mass of anhydrous ethanol is 1.5 times the mass of the cathode material precursor. The mixture is loaded into an agate ball mill jar and wet-milled at 250 rpm for 8 hours on a ball mill to ensure that MnO2 achieves micro-uniform and tight adsorption and coating on the surface of the lithium-ion cathode material particles. After drying at 120℃ for 2 hours, an intermediate product is obtained. (3) The intermediate product is transferred into an oxygen atmosphere furnace for further calcination to achieve solid-state lattice reconstruction. The calcination procedure is as follows: first, heat from room temperature to 500°C at a heating rate of 1°C / min and hold for 8 hours; then continue heating to 700°C at a heating rate of 1°C / min and sinter at high temperature for 18 hours. After cooling, the modified cathode material is obtained.
[0037] Comparative Example 1 This comparative example provides a method for preparing a cathode material, which is basically the same as that in Example 1, except that the addition of manganese dioxide is omitted. A scanning electron microscope image of the cathode material prepared in this comparative example is shown below. Figure 5 As shown.
[0038] Comparative Example 2 This comparative example provides a method for preparing a cathode material, including the following steps: (1) Same as step (1) in Example 1, to obtain the lithium-ion cathode material; (2) is basically the same as step (2) of Example 1, except that the addition of manganese dioxide is omitted to obtain the intermediate product; (3) The intermediate product was poured into deionized water at a solid-liquid mass ratio of 1:1, and the mixture was quickly stirred and washed for 5 minutes. Then, it was filtered and dehydrated. The filter cake was dried in a vacuum oven at 120°C for 12 hours. In order to repair the surface lattice damage caused by water washing, the dried solid was subjected to secondary solid-phase sintering at 500°C for 6 hours in a pure oxygen atmosphere to obtain the cathode material.
[0039] Comparative Example 3 This comparative example provides a method for preparing a modified cathode material, which is basically the same as that in Example 2, except that high-purity manganese dioxide is replaced with nano-alumina powder, and the molar ratio of total metal elements in the cathode material precursor to aluminum elements in alumina is kept at 1:0.03.
[0040] Comparative Example 4 This comparative example provides a method for preparing a modified cathode material, which is basically the same as that in Example 1, except that in step (2), the molar ratio of the total metal elements in the cathode material precursor to the manganese elements in manganese dioxide is adjusted to 1:0.01.
[0041] Comparative Example 5 This comparative example provides a method for preparing a modified cathode material, which is basically the same as that in Example 1, except that in step (2), the molar ratio of the total metal elements in the cathode material precursor to the manganese elements in manganese dioxide is adjusted to 1:0.06.
[0042] Experimental Example 1 1. The positive electrode materials obtained in each embodiment and comparative example are assembled into coin cells. The preparation method of the coin cells is as follows: (1) Preparation of positive electrode sheet: The positive electrode material (including conductive carbon black and carbon nanotubes with a mass ratio of 3.5:1) and the binder polyvinylidene fluoride obtained in each example and comparative example are mixed in a mass ratio of 94:3:3. N-methylpyrrolidone is added and mixed into a uniform slurry. The slurry is coated on aluminum foil, vacuum dried at 120°C for 12 hours, and then rolled to obtain the positive electrode sheet.
[0043] (2) Assembly of button cell: In an argon-protected glove box, using a positive electrode sheet (punched into a 12mm diameter disc) as the positive electrode, a lithium metal sheet as the negative electrode, Celgard 2400 as the separator, and 1mol / L LiPF6 as the electrolyte (the solvent is ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1), the negative electrode shell, negative electrode sheet, electrolyte, separator, positive electrode sheet, electrolyte, positive electrode shell, and sealing machine are placed in sequence to assemble a CR2032 button cell.
[0044] 2. Perform performance tests on the button cells prepared above. (1) Charge and discharge test: At 25℃, charge to 4.3V at a rate of 0.1C and then discharge to 3.0V at a rate of 0.1C. Record the first charge specific capacity and the first discharge specific capacity, and calculate the first coulombic efficiency according to (first discharge capacity / first charge capacity) × 100%.
[0045] (2) Cyclic performance test: At 25°C, the button cell was first activated at 0.1C for two cycles (i.e., charge and discharge for two cycles), and then charged and discharged at 0.5C for 100 cycles, with a voltage range of 3.0V-4.3V; the discharge specific capacity of the 100th cycle was recorded.
[0046] (3) Rate performance test: At 25℃, the button cell is first activated at 0.1C for two cycles (i.e., charge and discharge for two cycles), and then the button cell is charged and discharged at 5C for 5 cycles with a voltage range of 3.0-4.3V. The discharge specific capacity of each cycle is recorded, and the average value of the discharge specific capacity of 5 cycles is taken as the 5C rate discharge specific capacity.
[0047] 3. Test Results Table 1 Performance Test Results
[0048] As shown in Table 1, the modified cathode materials prepared in Examples 1-5 all exhibited high initial charge-discharge specific capacity and initial coulombic efficiency, and significantly improved the cycle stability and high-rate performance of the cathode materials. However, Comparative Example 1, without a manganese source, underwent direct secondary sintering, resulting in a high residual lithium content on the cathode material surface, leading to severe cycle degradation. While Comparative Example 2 eliminated residual lithium, water washing caused severe surface lithium loss, degrading to form a thick electrochemically inert rock salt phase, resulting in a significant decrease in initial charge-discharge specific capacity and initial coulombic efficiency, and significantly lower specific capacity after cycling and at high rates. Comparative Example 3 used alumina coating; however, Al… 3+ The addition of a manganese source to induce lattice reconstruction in Comparative Example 4 resulted in insufficient manganese source addition, which failed to activate the topological lithiation mechanism and prevented the conversion of residual lithium. Consequently, the first charge-discharge specific capacity, first coulombic efficiency, cycle performance, and rate performance could not be improved. This demonstrates that the addition of a manganese source to induce lattice reconstruction in this invention is irreplaceable. Although a manganese source was added in Comparative Example 5, the amount added was too small to activate the topological lithiation mechanism, and the residual lithium could not be converted, resulting in no significant improvement in first coulombic efficiency, rate performance, and cycle performance. An excessive amount of manganese source was added in Comparative Example 5, which formed a passivation layer on the surface of the cathode material, hindering lithium-ion transport and also leading to a significant reduction in first coulombic efficiency, rate performance, and cycle performance.
[0049] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a modified cathode material, characterized in that, Includes the following steps: Step S1: Mix the cathode material precursor and the lithium source in the first stage, and pre-calcine to obtain the lithium-ion cathode material; Step S2: The lithium-ion cathode material, manganese source and dispersant are mixed for the second time and dried to obtain the intermediate product; Step S3: Calcine the intermediate product to obtain the modified cathode material.
2. The method for preparing the modified cathode material according to claim 1, characterized in that, The molar ratio of total metal elements in the cathode material precursor to manganese elements in the manganese source is 1:0.02-0.05, preferably 1:0.03-0.
05.
3. The method for preparing the modified cathode material according to claim 1, characterized in that, The chemical formula of the cathode material precursor is Ni. x Co 1-x (OH)₂, where 0.9 ≤ x ≤ 0.94; And / or, the molar ratio of total metal elements in the cathode material precursor to lithium elements in the lithium source is 1:1.05-1.08, preferably 1:1.06; And / or, the lithium source includes lithium hydroxide monohydrate and / or lithium carbonate.
4. The method for preparing the modified cathode material according to claim 1, characterized in that, The mass ratio of the positive electrode material precursor to the dispersant is 1:1-1.5; And / or, the manganese source includes at least one of manganese dioxide, manganese hydroxide, and manganese hydroxyoxide; And / or, the dispersant includes at least one of ethanol, ethylene glycol, and polyvinyl alcohol.
5. The method for preparing the modified cathode material according to claim 1, characterized in that, The first mixing speed is 1000-1500 rpm, and the time is 20-30 min; And / or, the pre-calcination operation includes heating from room temperature to 300-400°C at a heating rate of 1-3°C / min under an oxygen atmosphere, and holding at that temperature for 4-8 hours; And / or, the second mixing speed is 250-350 rpm, and the time is 4-8 h; And / or, the drying temperature is 100-120℃ and the time is 2-4 hours; And / or, the calcination operation is to heat from room temperature to 500-600°C at a heating rate of 1-3°C / min under an oxygen atmosphere, hold at that temperature for 4-8 hours, and then continue heating to 700-800°C at a heating rate of 1-3°C / min, and hold at that temperature for 12-18 hours.
6. The modified cathode material prepared by the method of any one of claims 1-5.
7. The modified cathode material according to claim 6, characterized in that, The modified cathode material includes a cathode material matrix and a coating layer covering the surface of the cathode material matrix; the coating layer includes Li2NiO2 and / or Li2MnO3.
8. A positive electrode sheet, characterized in that, include: Positive current collector, and A positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a modified positive electrode material prepared by the preparation method according to any one of claims 1-5 or a modified positive electrode material according to claim 6 or 7.
9. A secondary battery, characterized in that, Includes the positive electrode sheet as described in claim 8.
10. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 9.